Evaluating the effects of oseltamivir phosphate on platelet counts: a retrospective review. (16th November 2020) - Shaim, Hila; McCaffrey, Peter; Trieu, Judy A; DeAnda, Abe; Yates, Sean G.
Abstract: Desialylation of platelets results in platelet clearance by the Ashwell-Morrell Receptors (AMR) found on hepatocytes. Studies suggest that oseltamivir phosphate inhibits human sialidases, enzymes responsible for desialylation, extending the lifespan of circulating platelets. We thus evaluated, the effects of oseltamivir on platelet count (PC) following treatment. Of the 385 patients evaluated for influenza, 283 (73.5%) were influenza-infected. Of the 283 infected patients, 241 (85.2%) received oseltamivir (I + O+) while 42 patients did not (I + O-). One hundred two non-infected patients received oseltamivir (I-O+). The two groups receiving oseltamivir (I + O+, I-O+), demonstrated a statistically greater increase in the PC (57.53 ± 93.81, p = .013 and 50.79 ± 70.59, p = .023, respectively) relative to the group that did not (18.45 ± 89.33 × 10 9 /L). The observed increase in PC was statistically similar ( p = .61) in both groups receiving oseltamivir (I + O+, I-O+), suggesting that this effect is independent of influenza. Comparing clinical characteristics between responders and non-responders to oseltamivir treatment showed that only duration of oseltamivir treatment (AOR = 1.30, 95% CI 1.05–1.61, p = .015) was associated with a positive PC response. Our findings suggest a correlation between oseltamivir treatment and an increase in PCs. Future studies assessing the possible uses of oseltamivir in medical conditions characterized by diminished or defective thrombopoiesis are warranted.